Biocompatibility, resorption and biofunctionality of a new synthetic biodegradable membrane for guided bone regeneration. (10th August 2016) - Hoornaert, Alain; d'Arros, Cyril; Heymann, Marie-Francoise; Layrolle, Pierre
Abstract: Membranes for guided bone regeneration (GBR) were prepared from the synthetic biodegradable polymer poly-D, L-lactic/glycolic acid (PLGA). This GBR membrane has a bi-layered structure with a dense film to prevent gingival fibroblast ingrowth and ensure mechanical function, and a micro-fibrous layer to support colonization by osteogenic cells and promote bone regeneration. Hydrolysis and biodegradation were both studied in vitro through soaking in phosphate buffered saline (PBS) and in vivo by implantation in the subcutis of rats for 4, 8, 16, 26, 48 and 52 weeks. Histology revealed an excellent colonization of the micro-fibrous layer by cells with a minimal inflammatory reaction during resorption. GBR using the synthetic PLGA membrane was evaluated on critical-size calvaria defects in rats for 4 and 8 weeks. Radiographs, micro-computed tomography and histology showed bone regeneration with the PLGA membrane, while the defects covered with a collagen membrane showed a limited amount of mineralized bone, similar to that of the defect left empty. The biofunctionality of the PLGA membranes was also compared to collagen membranes in mandible defects in rabbits, associated or not with beta-tricalcium phosphate granules. This study revealed that the bi-layered synthetic membrane made of PLGA was safer, more biocompatible, and had a greater controlled resorption rate and bone regeneration capacity than collagen membranes. This new PLGA membrane could be used in pre-implantology and peri-odontology surgery.